PENGARUH PIJAT BAYI TERHADAP LAMA TIDUR BAYI DI DESA DUWET KECAMATAN WONOSARI KABUPATEN KLATEN - Warsini Warsini; Dyah Nugraini (KOSALA : Jurnal Ilmu Kesehatan, 2016)
Background: Even the oldest massage is an activity used by humans to expelfatigue and stress. Lack of information and knowledge of parents of massage,makes many parents think a massage is not a scientific and natural form oftherapy for infants. Most mothers believe massage is necessary only when theirchild had flu and colds.Purpose of the study: To determine the effect of infant massage on infant sleepduration in the village of Duwet, Wonosari Subdistrict, Klaten Regency.The subject: The population in this study is a baby in the village of DuwetWonosari District of Klaten regency totaling 45 babies. Samples that met thestudy criteria and amounted to 20 babies. The sampling technique is simplerandom sampling.Methods: The data collection is done by the experimental method is bymeasuring how much sleep babies after intervention. Data were analyzed usingstatistical tests Independent t-test.The results: Long sleep in infants that give the infant massage is known that atleast 11 hours and a maximum of 18 hours with an average bed is 15.90 hours.Long sleep in infants who were not given the infant massage is known at least 12hours and a maximum of 17 hours with an average bed is 13.90 hours. Statisticalanalysis showed p: 3.967 with an upper limit 0.047 and lower limit 0.33.Conclusion: There is a statistically significant effect of infant massage with infantsleep duration (p: 3.967 with an upper limit 0.047 and lower limit 0.33).Keywords: infant massage, infant sleep duration